Atividade livre na caixa associada ao ganho de peso e restauração das propriedades estruturais e mecânicas de osso em ratos jovens após hiposinesia de membros pélvicos - Barbosa, Adelton Andrade; Del Carlo, Ricardo Junqueira; Galvão, Simone Rezende; Louzada, Mário Jefferson Quirino [UNESP]; Franco, Frederico Souzalima Caldoncelli; Fernandes, Bárbara Braga; Carneiro-Junior, Miguel Araújo; Ramos, Regiane Maria Soares; Drummond, Lucas Rios; Natali, Antonio Jose (My University, 2012)
We investigated the importance of daily free activity in the cage and body weight gain during the recovering of bone structural and mechanical properties in growing rats after hindlimb unloading. Eight-week-old male Wistar rats were randomly divided into control (CG, n=24) and suspended (SG, n=24) groups. Animals from SG underwent a four-week hindlimb unloading period by tail-suspension. Animals from CG and those from SG after release were kept in collective cages and sacrificed at the age of 12, 16 and 20 weeks. Both femurs were removed and its area, bone mineral density (BMD), resistance to failure and stiffness were determined. Four-week hindlimb unloading decreased (p<0.05) body weight (CG, 373.00 ± 9.47 vs. SG, 295.86 ± 9.19 g), BMD (CG, 0.19 ± 0.01 vs. SG, 0.15 ± 0.01 g/cm 2), bone resistance to failure (CG, 147.75 ± 5.05 vs. SG, 96.40 ± 5.95 N) and stiffness (CG, 0.38 ± 0.01 vs. SG, 0.23 ± 0.02 N/m). Eight weeks of free activity in cage recovered (p>0.05) the body weight (CG, 472.75 ± 14.11 vs. SG, 444.75 ± 18.91 g), BMD (CG, 0.24 ± 0.01 vs. SG, 0.22 ± 0.01 g/cm 2), bone resistance to failure (CG, 195.73 ± 10.06 vs. SG, 178.45 ± 8.48 N) and stiffness (CG, 0.56 ± 0.02 vs. SG, 0.47± 0.03 N/m) of SG animals. Body weight correlated strongly with bone structural and mechanical properties (p<0.0001). In conclusion, free activity in the cage associated with body weight gain restored bone structural and mechanical properties in growing rats after hindlimb unloading.
Free activity in the cage associated with body weight and restoration of bone structural and mechanical properties in growing rats after hindlimb unloading
Keywords: Bone mineral density; Bone stiffness; Osteopenia